2003
DOI: 10.1179/147842203225008921
|View full text |Cite
|
Sign up to set email alerts
|

Holistic model for atmospheric corrosion: Part 3 - Effect of natural and man made landforms on deposition of marine salts in Australia and south-east Asia

Abstract: This paper present results from a large number of airborne salinity measurements in Australia and south-east Asia (SEA). Salinity measurements were made in the open on clear ground, in the open in urban regions, and on the facades of buildings. The data were used to assess the validity of the concepts regarding saline sources and transport presented in previous papers. In particular, the salinity measurements in SEA are used to assess the validity of the models for ocean produced salt aerosol. A classi cation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 4 publications
1
28
0
Order By: Relevance
“…The model predicts the transport 2 and deposition of marine aerosols 3, the response of metal surfaces to aerosol deposition 4–6 and climatic conditions 7, and lastly mass loss. The model has been validated in Australia and South‐East Asia 8, 9, but not the Middle East.…”
Section: Introductionmentioning
confidence: 99%
“…The model predicts the transport 2 and deposition of marine aerosols 3, the response of metal surfaces to aerosol deposition 4–6 and climatic conditions 7, and lastly mass loss. The model has been validated in Australia and South‐East Asia 8, 9, but not the Middle East.…”
Section: Introductionmentioning
confidence: 99%
“…As shown inTable 1, chloride concentration measured in the Province of Western Coast (Red Sea) is generally high.Frasan, Hakal and Wajah shows the highest salinity values: 740, 704 and 608 mg m 22 d 21 Cl 2 respectively, which belong to categories S 3 (the rest belong to S 2 ). These results show that atmospheric salinity depends on the wind pattern at each specific site 10,[29][30][31][32][33][34][35][36]. The main part of anthropogenic SO 2 pollution is caused by combustion of fossil fuels and algae decomposition.…”
mentioning
confidence: 99%
“…The plot demonstrates the rapid fall off in deposition with increasing number of houses. Such a fall off was observed experimentally and is reported in Cole et al 3 In fact, Cole et al 3 found that salinity on the facade of a dwelling in a general urban area would be reduced to around 25% of that on a salt candle at an equivalent distance from the coast on clear (low roughness) ground. The data presented in Fig.…”
Section: Deposition On Buildingsmentioning
confidence: 76%
“…If R s is low, the value of R a determines V d . V d is determined from an analogy with momentum transport, which gives V d~u 2 Ã =U : : : : : : : : : : : : : : (3) where U is the upstream velocity, and u* is the average 'friction velocity' in the local boundary layer. u 2 Ã is proportional to the local turbulent kinetic energy in the boundary layer and thus depends on the size of the obstacle.…”
Section: Introductionmentioning
confidence: 99%